Aplikasi Monitoring Perkembangan Level Terapi Untuk Anak Gangguan Autis Usia Dini - Maslihah; Khoirul Huda (Melek IT : Information Technology Journal, 2016)
Autism is a complex developmental disorder that is associated with communication , social interaction and activity of the imagination . The lack of knowledge of parents in responding to children with autism , children with autism make only left alone without any serious treatment , so that children with autism neglected . One alternative that could be used to develop the potential of children with autism or that children with autism can live independently by using therapies to facilitate treatment development. So that parents know more about the development of the child's completion of therapy , then by this researcher has an idea that makes monitoring system that can be accessed parents to know their children after completion penerapian that will be monitored . This research aims to create a same practice Monitoring Information For Children Autistic Disorders In Early Childhood , using Method Prototype .